Analisis Return On Equity (ROE) Bank Mega Syariah 2020-2024 dalam kerangka manajemen risiko perbankan syariah - nisa, siti khoirun; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
Return on Equity (ROE) is a key indicator used to assess a bank’s ability to generate profit from its existing capital. In Islamic banks, ROE is particularly important not only for measuring profitability but also for reflecting the effectiveness of risk management in handling financing activities, liquidity conditions, and operational efficiency. This article analyzes the ROE of Bank Mega Syariah for the period 2020–2024 using data from the bank’s annual reports and theoretical foundations from academic literature. The analysis shows that the ROE of Bank Mega Syariah experienced significant fluctuations: 9.76% (2020), 28.48% (2021), 11.73% (2022), 9.76% (2023), and 9.81% (2024). These changes were influenced by the pandemic, cost-efficiency measures, financing quality, and capital structure. The findings highlight the need for strengthened risk management, increased digitalization, income diversification, and capital optimization to enhance sustainable profitability.